Legal Regime of the Protected Natural Areas Under Directives 92/43/EEC and 2009/147/EC of the European Union - Penchev, Georgi (Research Papers, 2021)
Basic aim of this study is analysis of the protection of biological diversity in protected natural territories under Directives 92/43/EEC and 2009/147/EC. These legal acts of the European Union are related to the protection of species of wild flora and fauna and natural habitats. The basic task of the study consists in consideration of the legal measures in this field under these directives in the context of their introduction in the Bulgarian legislation. The comparative law and formal-logical methods of scientific research are used. The result of study is related to formulation of general conclusions from considered legal regulation and suggestions for its improvement.